Micro-network creation in industrial surveying - Pospíšilová, Lucie; Pospíšil, Jiří; Staňková, Hana (Geodesy and Cartography, 2012)
Industrial surveying is special field of work within engineering surveying. In this article we have documented some procedures and principles which are very special in industrial surveying. A micro-network consists of net points which are set as a base for all surveying in the industry. These points create coordinate system for all measured parts of the machine. For realization of micro-network are used well known geodetic methods such as triangulation, trilateration, levelling or trigonometric high. As horizontal and vertical controls do not exist in a factory hall, a surveyor has to find some different method to start working.